The Effects of Price and Wage Flexibility on Cyclical Contraction - Fels, Rendigs (Quarterly Journal of Economics, 1950)
Introduction, 596. — I. Wage flexibility, 599. — II. Flexibility of the unit overhead-plus-profit margin, 603. — III. Price flexibility in particular types of industries, 604. — IV. Some historical cases, 606.